Establishing diagnostic criteria for feline obesity using a highly sensitive serum amyloid A assay - Kobayashi, Miki; Kobayashi, Motoo; Hirose, Tomoaki; Yuki, Masashi; Imano, Satoru; Asahi, Yukari; Teshima, Takahiro; Arai, Toshiro (Frontiers in Veterinary Science, 2025)
IntroductionThe global increase in the prevalence of overweight and obesity is associated with several chronic diseases. Obesity is characterized by systemic low-grade inflammation and oxidative stress caused by excessive fat accumulation. This study aimed to establish diagnostic criteria for pathological obesity in cats using a highly sensitive serum amyloid A (SAA) assay.MethodsIn this study, 29 client-owned cats (3–14 years old) with varying body condition scores (BCS) were included. These cats underwent medical checkups and were not treated for any specific diseases. They were divided into three groups: healthy control, simple obesity, and obesity disease. The plasma levels of metabolites, hormones, and enzymes were measured.ResultsIn the simple obesity cats, body weight, BCS, and plasma triglyceride (TG) and malondialdehyde (MDA) concentrations were significantly higher than those in the healthy control cats. In the obesity disease cats, BCS was significantly higher than that in the simple obesity cats, and plasma TG and SAA concentrations and alanine aminotransferase (ALT) activities increased significantly compared to those in the simple obesity cats. Adiponectin concentrations in the obesity disease cats were significantly lower than those in the healthy control cats.DiscussionThe novel criteria for feline obesity (overweight cats exhibiting two or more of the following symptoms: hyperlipidemia and high ALT and SAA levels) were based on biomarker values that were significantly higher than those in the simple obesity cats. These novel criteria may help detect pathological obesity at an early stage. Early and accurate diagnosis can prevent age-related diseases including obesity.